Evaluating the effect of complete denture in correct pronunciation of speech sounds - A. Fazel; R. Mosharaf (Tehran University of Medical Sciences, 1997)
Although a full denture cab  replace the teeth and their supporting structures , it commonly develops temporary speech problems that are resolved after a while. In this study, 70 patients were recruited from Prosthodontics department of Tehran and Isfahan dental schools. The patients were analyzed via special questionnaires and oral interview by gender, previous prosthesis and  in 3 phases of edentulous, immediately after denture delivery and a week after delivery. Following data gathering and statistical analysis, it was found that "sh", "s"," Ch" sounds are the most and " m" is the least difficult sound to  pronounce. The study results showed significant difference between 3 stages of denture usage. Also, the effect of previous prosthesis on speech was concluded while gender had not any relation with speech problems.